PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDA SOSIAL DALAM MEMBENTUK KARAKTER GENERAS Z DI MADRASAH ALIYAH RADEN RAHMAT MOJOWARNO JOMBANG - Irma Uswatun Ummah; Maskuri Maskuri; Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Education has recently been shaken by the COVID-19 virus. The existence of thevirus has had a significant impact on education in Indonesia. The impact of exposureto the virus is that education inevitably has to innovate the learning process intoonline learning. This is done to prevent the spread of the Covid-19 virus. Theenactment of online learning then becomes a foothold for researchers in exploringhow the process of forming the character of Generation Z is in it. This research is acase study research with a qualitative descriptive approach. Sources of data in thisstudy include primary and secondary data. The data collection used the observationmethod conducted at the Madrasah Aliyah Raden Rahmat and interviews with thefocus of the subject, namely the principal, waka of the curriculum, and teachers ofIslamic religious education. The results of this study can be concluded as follows: 1)in planning, starting from making or developing a curriculum, making a syllabus,making lesson plans for each meeting, and learning strategies. 2) implementation ofonline learning using zoom meeting media, whatsapp video, instagram, andyoutube. 3) the learning model used is a blended learning model. Characterformation is carried out through habituation of students by praying before startinglessons, reading Asmaul Husna, on certain days reading Yasin or Waqi'ah letters. Inaddition, the madrasah always coordinates with the parents of students to seedevelopments during online learning.